2017
DOI: 10.1590/1414-462x201700020272
|View full text |Cite
|
Sign up to set email alerts
|

Produção e avaliação comparativa de preços de produtos do Laboratório de Manipulação Farmacêutica - Ribeirão Preto – SP: experiência relacionada à Assistência Farmacêutica no SUS

Abstract: Resumo Introdução A Assistência Farmacêutica prestada pelo setor público de saúde deve também compreender a produção de medicamentos. Sendo assim, realizou-se estudo relacionado às atividades do Laboratório de Manipulação Farmacêutica da Secretaria da Saúde de Ribeirão Preto, SP. Métodos Foi realizada pesquisa quantitativa com informações das fichas de produção, entre 2006 a 2015, e comparação entre os preços de mercado e aqueles dos produtos com maior demanda produzidos (12/2015). Resultados Os resultados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…In another service connected to a compounding pharmacy of the health department, Borrella and Pereira (2017) showed that besides the large production capacity of a public pharmacy (34 thousand units in 2015), the unit cost of production for the state was between 186%-802% lower than the potential purchase from private pharmacies (Borella, Pereira, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In another service connected to a compounding pharmacy of the health department, Borrella and Pereira (2017) showed that besides the large production capacity of a public pharmacy (34 thousand units in 2015), the unit cost of production for the state was between 186%-802% lower than the potential purchase from private pharmacies (Borella, Pereira, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of a public policy to encourage and to finance the production of manipulated medicines in SUS, the practice is already used in some health units through specific initiatives of states and municipalities, which acquire the medicines through public bidding or pharmaceutical production, the latter being a more common practice in hospital units [ 13 ]. Among the manipulation experiences in the public network, the one carried out in the city of Ribeirão Preto stands out, where the Pharmaceutical Manipulation Laboratory produces 46 presentations for SUS patients [ 39 ]. For the Tuberculosis Program, 3% sodium chloride was produced for inhalation, used as a stimulus for pulmonary secretions before collecting material for examination, for the Leprosy program, an ethyl ether:ethane mixture was produced, used to test the sensitivity of the skin on regions affected by the disease [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the manipulation experiences in the public network, the one carried out in the city of Ribeirão Preto stands out, where the Pharmaceutical Manipulation Laboratory produces 46 presentations for SUS patients [ 39 ]. For the Tuberculosis Program, 3% sodium chloride was produced for inhalation, used as a stimulus for pulmonary secretions before collecting material for examination, for the Leprosy program, an ethyl ether:ethane mixture was produced, used to test the sensitivity of the skin on regions affected by the disease [ 39 ]. The vast majority of the presentations produced, however, are for topical use, such as 2% acetic acid solution and sunscreen [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No decorrer desse período, sempre houve intenção de adequação às novas legislações que entraram em vigor (RDC 67/2007, RDC 18/2013). Houve, também, por parte dessa unidade, o comprometimento em relação ao desenvolvimento de novas técnicas de produção e metodologias analíticas através do desenvolvimento de projetos de pesquisa em associação com a Universidade de Ribeirão Preto (UNAERP) e, eventualmente, com apoio financeiro da Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP) (13). Foi através dessas oportunidades de parcerias que houve condições para o desenvolvimento de ações relacionadas com o controle de qualidade dos insumos e produtos preparados.…”
Section: Introductionunclassified